Investigation of hot mixture asphalt with high ground tire rubber content. (20th December 2020) - Chen, Siyu; Ge, Dongdong; Jin, Dongzhao; Zhou, Xiaodong; Liu, Chaochao; Lv, Songtao; You, Zhanping
Abstract: Stockpiles of waste tires pose concerns of potential contamination of local groundwater, and fire risk from the large amounts of tires. To sustainably use the waste tires, Ground Tire Rubber (GTR) that produced from waste tires has been used in the pavement industry for decades. The typical GTR content is approximately 1–3% by weight of the asphalt mixture. To utilize more waste tires, there is an increasing demanding of using higher amount of GTR in recent years. The objective of this study was to determine the high GTR content that can be used in the asphalt pavement without sacrificing performance. In this study, gap-graded mixtures modified with differing GTR contents were designed. These GTR contents were 2.6%, 3.4%, 3.7%, 4.1% and 4.5% by weight of the mixture. Statistical analysis was conducted to determine the influence of GTR content on the mixture performance. It was found that the fracture energy of the GTR modified mixture was two to three times higher than that of the control mixture. All of the mixtures seemed to provide adequate rutting resistance for low-volume traffic, signifying that after 5000 wheel passes, the rutting depth did not exceed the 12.5-mm. The GTR modified gap-graded mixtures had high resistance to low-temperature cracking and high-temperature rutting. This can partly be attributed to the addition of GTR and the skeleton structure from gap gradation. The result of multiple comparisons suggested that even though the addition of GTR in dense-graded mixtures did not significantly improve the high-temperature performance, the addition of GTR in asphalt mixtures significantly improved the low-temperature performance.